Molecular phylogenetics of the African horseshoe bats (Chiroptera: Rhinolophidae): expanded geographic and taxonomic sampling of the Afrotropics - Terrence C. Demos; Paul W. Webala; Steven M. Goodman; Julian C. Kerbis Peterhans; Michael Bartonjo; Bruce D. Patterson (BMC Evolutionary Biology, 2019)
Abstract Background The Old World insectivorous bat genus Rhinolophus is highly speciose. Over the last 15 years, the number of its recognized species has grown from 77 to 106, but knowledge of their interrelationships has not kept pace. Species limits and phylogenetic relationships of this morphologically conservative group remain problematic due both to poor sampling across the Afrotropics and to repeated instances of mitochondrial-nuclear discordance. Recent intensive surveys in East Africa and neighboring regions, coupled with parallel studies by others in West Africa and in Southern Africa, offer a new basis for understanding its evolutionary history. Results We investigated phylogenetic relationships and intraspecific genetic variation in the Afro-Palearctic clade of Rhinolophidae using broad sampling. We sequenced mitochondrial cytochrome-b (1140 bp) and four independent and informative nuclear introns (2611 bp) for 213 individuals and incorporated sequence data from 210 additional individuals on GenBank that together represent 24 of the 33 currently recognized Afrotropical Rhinolophus species. We addressed the widespread occurrence of mito-nuclear discordance in Rhinolophus by inferring concatenated and species tree phylogenies using only the nuclear data. Well resolved mitochondrial, concatenated nuclear, and species trees revealed phylogenetic relationships and population structure of the Afrotropical species and species groups. Conclusions Multiple well-supported and deeply divergent lineages were resolved in each of the six African Rhinolophus species groups analyzed, suggesting as many as 12 undescribed cryptic species; these include several instances of sympatry among close relatives. Coalescent lineage delimitation offered support for new undescribed lineages in four of the six African groups in this study. On the other hand, two to five currently recognized species may be invalid based on combined mitochondrial and/or nuclear phylogenetic analyses. Validation of these cryptic lineages as species and formal relegation of current names to synonymy will require integrative taxonomic assessments involving morphology, ecology, acoustics, distribution, and behavior. The resulting phylogenetic framework offers a powerful basis for addressing questions regarding their ecology and evolution.